Charles Clinch Bubb and the Clerks Press. - Robert G. Cheshier (Toledo The Ward M. Canaday Center, 1986)
The library of the Cleveland Museum of Art contributed a small box of private press publications to the library of the Rowfant Club. These were the impressive works of the Clerk`s Press, a labor of love of Charles Clinch Bubb, or Canon Bubb as he preferred to be called.
Keywords: Science